Pengaruh Audit Tenure, Auditor Switching dan Opini Audit terhadap Audit Report Lag - Wini Julia Abbet; Enggar Diah Puspa Arum; Wiralestari Wiralestari (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study aims to analyze the effect of audit tenure, auditor switching, and audit opinion on audit report lag in energy sector companies listed on the IDX for the 2020–2023 period. This study uses a quantitative approach with secondary data obtained from the company's annual report available on the official IDX website and related company websites. The sample used a purposive sampling method, with a total of 208 financial reports from 90 energy sector companies that met the research criteria. The data analysis methods used include descriptive statistics, classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation), and multiple linear regression analysis with the help of SPSS version 25 software. The results of the study reflect that partially, audit tenure, auditor switching and audit opinion have a significant effect on audit report lag. Simultaneously, the three independent variables have a significant effect on audit report lag.